Resistensi Terbuka International Freedom Battalion (IFB) terhadap ISIS di Suriah - Falhan Hakiki (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2019)
This article aims to find out the resistance of the International Freedom Battalion (IFB) movement against Islamic State of Iraq and Suriah (ISIS) in Syria. Through qualitative research methods with an analytical descriptive approach, and also the conceptual framework of social movements and resistance, can be identified and explained the forms of actions carried out by IFB to resist ISIS domination in Syria. The author found that the existence of IFB resistance to ISIS was motivated by the existence of three dominations carried out by ISIS, namely material domination, status domination, and ideological domination. IFB resistance measures include two elements in it, namely action and opposition. Action from IFB's resistance action in the form of a series of military actions in 2015-2017 against three ISIS dominations. While opposition from IFB's resistance actions included resistance to the occupation of the territory carried out by ISIS, resistance to the stamp of takfiri ISIS, and resistance to the ideology of the new style of ISIS in order to defend the Rojava Revolution.